Research priorities: Strengthening Gender Intentionality and Accelerating Broad, Equitable Impacts of Genetic Innovations - Ragasa, Catherine; Tenneti, Suchaita; Bomuhangi, Allan; Mulwa, Chalmers; Najjar, Dina; Pazos, Mateo; Polar, Vivian; Teeken, Bela; Yila, Jummai (CGIAR System Organization, 2025)
Genetic innovations hold immense potential to address many global challenges and contribute to income generation opportunities, food and nutrition security, reduced environmental pressure, and climate resilience. However, the current rates of genetic innovation take-up, scaling, and impacts are slow and uneven (Walker et al. 2015; Fuglie and Rada 2016; He and Li 2020; Wollburg et al. 2024). Many studies have highlighted the disproportionate lack of access by women and other vulnerable groups to these innovations, and their limited participation and agency in the institutions that govern the design and delivery of these innovations (FAO 2023; Njuki et al. 2025; Puskur et al. 2021). This brief identifies key knowledge gaps and frontier research ideas to achieve broad, gender-equitable impacts from genetic innovation and seed systems development. It is primarily intended to provide recommendations to the new Science Program on Breeding for Tomorrow (B4T). The brief builds on the Genetic Innovation Gender Strategy (2024–2028), which establishes a roadmap for “best bet” investments in gender-intentional breeding, and priorities for gender research (Ashby et al. 2024). It elaborates on several of the Gender Strategy’s priorities and adds recommendations to advance a gender research agenda that could empower women and other marginalized farmers as partners in genetic innovations and seed systems development.